2007
DOI: 10.1111/j.1440-1681.2007.04606.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Characterization of a Repeated Acute Joint Inflammation Model in Rats

Abstract: 1. Chronic pain owing to arthritis is a major clinical problem worldwide. To study the underlying pathological mechanisms of chronic pain and the effectiveness of different treatments, a number of experimental models have been developed over the years. 2. We introduced a new subchronic inflammatory model by repeated unilateral administration of carrageenan into the ankle joint of rats, and investigated the degree and the time-course of the oedema, and thermal and mechanical hyperalgesia. 3. Carrageenan (450 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Knee swelling, which is an objective parameter of joint inflammation, was significantly reduced with both the oral and the EP-enhanced diclofenac treatment. 48 Again, this increased volume was significantly reduced by both oral and EP-enhanced diclofenac treatments 48 h after arthritis induction.…”
Section: Discussionmentioning
confidence: 91%
“…Knee swelling, which is an objective parameter of joint inflammation, was significantly reduced with both the oral and the EP-enhanced diclofenac treatment. 48 Again, this increased volume was significantly reduced by both oral and EP-enhanced diclofenac treatments 48 h after arthritis induction.…”
Section: Discussionmentioning
confidence: 91%
“…Carrageenan may induce a highly reproducible local antigenic response and its effects were reported in many studies. 5,18,19,20 A single local injection of 1% carrageenan results in an inflammatory reaction in the TMJ and periarticular tissues, with hyperplasia of the synovial membrane. 7 The dose and dilution of carrageenan used in this study were reported in previous studies that proved its inflammatory effect.…”
Section: Discussionmentioning
confidence: 99%
“…4 Carrageenan is a polysaccharide widely used for the induction of experimental inflammation on animal models, and it is the most common method for drug testing or assessment of new anti-inflammatory therapies. 5 Some studies have reported the successful utilization of this model to induce both rat paw and joint inflammation. 6,7 Alterations of the synovial membrane have been reported in cases of osteoarthritis of the TMJ.…”
Section: Introductionmentioning
confidence: 99%
“…Both types of phototherapy have been suggested for the treatment of inflammatory joint conditions due to the absence of side effects, which are common with the use of non-steroidal anti-inflammatory drugs (NSAIDs) [ 20 ]. Studies have reported that lasers and LEDs operating with similar parameters produce equivalent effects [ 21 , 22 ]. Different theories have been proposed to explain the analgesic action of phototherapy, but no consensus has been reached.…”
Section: Introductionmentioning
confidence: 99%